Plant stomatal closure improves aphid feeding under elevated CO 2 - Yucheng Sun; Huijuan Guo; Liang Yuan; Jianing Wei; Wenhao Zhang; Feng Ge (Global Change Biology, 2015)
Stomata help plants regulate CO 2 absorption and water vapor release in response to various environmental changes, and plants decrease their stomatal apertures and enhance their water status under elevated CO 2 . Although the bottom‐up effect of elevated CO 2 on insect performance has been extensively studied, few reports have considered how insect fitness is altered by elevated CO 2 ‐induced changes in host plant water status. We tested the hypothesis that aphids induce stomatal closure and increase host water potential, which facilitates their passive feeding, and that this induction can be enhanced by elevated CO 2 . Our results showed that aphid infestation triggered the abscisic acid ( ABA ) signaling pathway to decrease the stomatal apertures of Medicago truncatula , which consequently decreased leaf transpiration and helped maintain leaf water potential. These effects increased xylem‐feeding time and decreased hemolymph osmolarity, which thereby enhanced phloem‐feeding time and increased aphid abundance. Furthermore, elevated CO 2 up‐regulated an ABA ‐independent enzyme, carbonic anhydrase, which led to further decrease in stomatal aperture for aphid‐infested plants. Thus, the effects of elevated CO 2 and aphid infestation on stomatal closure synergistically improved the water status of the host plant. The results indicate that aphid infestation enhances aphid feeding under ambient CO 2 and that this enhancement is increased under elevated CO 2 .